1994
DOI: 10.1159/000171461
|View full text |Cite
|
Sign up to set email alerts
|

Sulindac Therapy of Colorectal Polyps in Familial Adenomatous Polyposis

Abstract: Familial adenomatous polyposis (FAP) is characterized by multiple adenomatous colorectal polyps, some of which progress to adenocarcinoma in the absence of surgery. Colectomy with ileorectal anastomosis still remains much in use, although strict surveillance of the rectal stump is necessary to prevent rectal cancer. After 1983, sulindac has been used to control rectal polyps in about 90 FAP patients, at doses of 150-400 mg/day. The treatment was well tolerated, and regression of the polyps was frequently obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The treatment was usually well tolerated, and regression of the polyps was frequently observed. Randomized double-blind, placebo-controlled studies showed a statistically significant decrease in the number and size of polyps after a few months of therapy [26], although with long-term treatment a proliferation of new polyps and cancer can occur [27,28]. Our intention was to use Sulindac treatment with IRA to decrease or avoid adenomas in the rectal stump.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment was usually well tolerated, and regression of the polyps was frequently observed. Randomized double-blind, placebo-controlled studies showed a statistically significant decrease in the number and size of polyps after a few months of therapy [26], although with long-term treatment a proliferation of new polyps and cancer can occur [27,28]. Our intention was to use Sulindac treatment with IRA to decrease or avoid adenomas in the rectal stump.…”
Section: Discussionmentioning
confidence: 99%
“…These are precursor lesions of large bowel cancer in people with familial adenomatous polyposis (FAP) [24,25]. Lovastatin (4), 2-methylbutanoic acid 1,2,3,7,8,8a-hexahydro-3,7-dimethyl-8-[2-(tetrahydro-4-hydroxy-6-oxo-2H-pyran-2-yl)ethyl]-1-naphthalenyl ester (Mevacor®) was one of the original HRIs used to reduce serum cholesterol levels in people with coronary artery disease.…”
Section: Sulindac With Lovastatinmentioning
confidence: 99%
“…At least four reports have documented incident cancer cases occurring among FAP patients while on sulindac. 95,57,61,68,91 In the most recent example, Giardiello et al 68 described an FAP patient treated with sulindac for 35 months who developed an ulcerating, flat rectal adenocarcinoma in the absence of neighboring polyps. Such cases highlight the fact that an accurate estimate of long-term colorectal cancer risk reduction from sulindac in individuals with FAP cannot currently be made.…”
Section: Potential Limitations Of Chemoprevention In Hereditary Colormentioning
confidence: 99%